Titanium-based photo-thermal fabric with super-hydrophobic surface and preparation method thereof

By spraying TiN and Janus particles on cotton fabrics, titanium-based photothermal fabrics with superhydrophobic, photothermal conversion and photocatalytic properties are prepared, which solves the problem of difficult to suppress ice accumulation in extreme environments in the prior art, and achieves efficient active deicing and self-cleaning effects.

CN119711160APending Publication Date: 2025-03-28TIAN JIN GONG YE DA XUE SHAO XING KE QIAO YAN JIU YUAN
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411883801.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing superhydrophobic surfaces are difficult to effectively inhibit ice accumulation caused by supercooled water droplet adhesion and frost in extreme environments, and lack the ability to actively de-icing.

Method used

Titanium-based photothermal fabrics with superhydrophobic, photothermal conversion and photocatalytic properties were prepared by spraying materials such as TiN and Janus particles (H-SiO2-TiO2 JPs) onto cotton fabrics. The fabric increases the surface temperature of the fabric through light-heat conversion, achieving active deicing effect.

Benefits of technology

It effectively prevents the droplets from freezing into ice in extreme environments, improves the deicing efficiency, and has self-cleaning ability, and enhances the anti-icing effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119711160A_ABST
    Figure CN119711160A_ABST
Patent Text Reader

Abstract

The invention discloses a titanium-based photo-thermal fabric with a super-hydrophobic surface and a preparation method of the titanium-based photo-thermal fabric, and the preparation method comprises the following steps: on the basis of optimal parameters, titanium nitride (TiN) is dispersed in ethanol, and after ultrasonic treatment, the titanium nitride (TiN) is sprayed on a cotton fabric of 10 * 10 cm to obtain a TiN coated cotton fabric. And then putting the fabric into a drying oven, and heating to quickly volatilize the ethanol, so that the obtained coating is more uniform. And adding polydimethylsiloxane (PDMS) and a curing agent into n-heptane, stirring, spraying with a PDMS solution for the second time, and putting into a drying oven. And finally, dispersing a certain amount of Janus particles (H-SiO2-TiO2JPs) into ethanol, and carrying out third spraying by using the ethanol. The super-hydrophobic photocatalytic fabric with the photothermal conversion performance is obtained after multiple times of spraying. According to the work, a new solution is provided for expanding the application range of the cotton fabric and solving various problems in different fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of textile fabrics, and specifically relates to a method for preparing a titanium-based anti-icing / de-icing photothermal fabric with a super-hydrophobic surface. Background Art

[0002] Ice and frost are common natural phenomena, and the accumulation of ice and frost affects all aspects of human life. Ice formation in industrial facilities can cause serious safety problems and huge economic losses; in cold environments, work clothes are prone to ice formation, which affects human activities, thereby reducing work efficiency or endangering human health. Although superhydrophobic surfaces can effectively delay or prevent the nucleation of original ice, due to the single application mode, they may not be enough to inhibit ice accumulation caused by supercooled water droplet adhesion and frost in extreme environments. In order to further improve the deicing effect, solar energy in nature can be used to increase the surface temperature of the substrate through the photothermal conversion performance of the material to achieve the purpose of active deicing. The prepared multifunctional coated fabric will provide new insights into the synergistic anti- / deicing effects of hydrophobicity, efficient photothermal conversion, and photocatalytic performance. Summary of the invention

[0003] In view of the shortcomings of the prior art, the object of the present invention is to provide a method for preparing a titanium-based anti-icing / de-icing photothermal fabric with a super-hydrophobic surface.

[0004] Another object of the present invention is to provide a titanium-based photothermal fabric having a super-hydrophobic surface obtained by the above preparation method.

[0005] The purpose of the present invention is successfully achieved through the following technical solutions.

[0006] A titanium-based photothermal fabric with a super-hydrophobic surface and a preparation method thereof, comprising the following steps:

[0007] 1) A certain amount of TiN is dispersed in ethanol, and is fully dissolved by ultrasonication, and then is uniformly sprayed on cotton fabric to obtain TiN-coated cotton fabric, which is named TiN-CF. The ratio of TiN to ethanol is (1.6-2.5): (97.5-98.4) by mass.

[0008] In the step 1), the ultrasonic time is 20 to 30 minutes;

[0009] In the step 1), the cotton fabric has a size of 10×10 cm.

[0010] 2) The TiN-CF fabric obtained in step 1) is placed in an oven for heating to allow the ethanol to evaporate quickly, so that the coating is more uniform. PDMS and curing agent are added to n-heptane and stirred. Then the PDMS mixed solution is sprayed evenly for the second time and placed in an oven for pre-baking.

[0011] In the step 2), the oven temperature is 80-100°C;

[0012] In the step 2), the oven heating time is at least 5 minutes;

[0013] In the step 2), the mass ratio of PDMS, curing agent and n-heptane is 10:1:34;

[0014] In the step 2), the stirring time is at least 0.5h;

[0015] In the step 2), the secondary oven temperature is 80-100°C;

[0016] In the step 2), the secondary oven time is at least 20 minutes.

[0017] 3) A certain amount of Janus particles (H-SiO2-TiO2 JPs) were dispersed in ethanol, stirred at room temperature to fully dissolve, and then sprayed evenly for the third time. After multiple spraying, a super-hydrophobic photocatalytic fabric with photothermal conversion performance was obtained, named TiN-SCF. The ratio of H-SiO2-TiO2 JPs to ethanol was (0.25-1.75): (98.25-99.75).

[0018] In the step 3), the stirring time is 1 to 2 hours.

[0019] The titanium-based photothermal fabric with a super-hydrophobic surface obtained by the above preparation method.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] (1) A titanium-based photothermal cotton fabric with a superhydrophobic surface was prepared by a simple spraying method. Janus particles have different physical and chemical properties on both sides, creating a unique micro-nano hierarchical structure in the coating, which helps to achieve superhydrophobicity. The excellent superhydrophobicity makes the fabric surface have a lower solid-liquid contact area, which can effectively reduce the heat exchange rate and reduce the nucleation sites for droplets to grow into ice crystals, achieving an anti-icing effect.

[0022] (2) TiN in the titanium-based photothermal cotton fabric with superhydrophobic surface is a low surface energy material that can utilize solar energy in nature and increase the surface temperature of the fabric through the photothermal conversion performance of the material to achieve the purpose of active deicing. After irradiation, the interaction between TiN and light at its resonant wavelength is significantly enhanced, thereby efficiently collecting light energy.

[0023] (3) The photocatalytic performance of titanium-based photothermal cotton fabric with super-hydrophobic surface showed a high degradation rate of Rhodamine B dye under simulated sunlight, showing good self-cleaning ability and achieving a self-cleaning effect. The photocatalytic performance helps to decompose some organic stains, and the synergy with hydrophobicity and photothermal performance can achieve a better anti-icing / de-icing effect.

[0024] The titanium-based photothermal cotton fabric with super-hydrophobic surface utilizes the solar energy in nature and increases the surface temperature of the substrate through the photothermal conversion performance of the material, effectively delaying or preventing the nucleation process of droplets freezing into ice, achieving the purpose of active deicing, and avoiding the impact of frost accumulation on clothing on human activities. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The schematic diagram is a preparation process of the super-hydrophobic photocatalytic fabric of the present invention and a photothermal anti-icing / de-icing application diagram;

[0026] Figure 2 The temperature variation curves of pure cotton fabric (CF) and JPs coatings containing different mass fractions of H-SiO2-TiO2;

[0027] Figure 3 The temperature variation curve of TiN-SCF under different light intensities;

[0028] Figure 4 The temperature change curve of TiN-SCF during the on-off light cycle;

[0029] Figure 5 These are photos of different droplets on the surface of Example 7 of the present invention;

[0030] Figure 6 is the removal rate of rhodamine B in Example 7 of the present invention;

[0031] Figure 7 The changing process of water drop freezing on different fabric surfaces;

[0032] Figure 8 is the ice adhesion strength of different fabrics;

[0033] Fig. 9 A schematic diagram of photothermal deicing of TiN-SCF and CF surfaces under sunlight;

[0034] Fig.10 Immersion test and UV aging test were performed on different solutions of Example 7 of the present invention; DETAILED DESCRIPTION

[0035] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0036] The preparation method of Janus particles (H-SiO2-TiO2 JPs) in step 3) can be adopted from the literature: Pakdel, E., Zhao, H., Wang, J. et al. Superhydrophobic and photocatalytic self-cleaning cotton fabric using flower-like N-doped TiO2 / PDMS coating. Cellulose 28, 8807–8820 (2021). https: / / doi.org / 10.1007 / s10570-021-04075-3

[0037]

[0038]

[0039]

[0040] Performance measurement:

[0041] Photocatalytic test: Take 3×2cm of fabric and put it into 100ml of Rhodamine B solution (10mg / L), stir it for 0.5h in a dark environment to reach adsorption equilibrium, then place it under a xenon lamp (with a cutoff plate, only ultraviolet light) for irradiation, take 3ml of solution at regular intervals, and test the sample absorbance by UV-visible spectrophotometer. Since the fabric is hydrophobic and not easy to contact with Rhodamine B solution, it is wetted with ethanol before testing.

[0042] Photothermal conversion performance test: The photothermal performance test experimental system consists of a xenon lamp and an infrared thermal imager. The sample is placed on an A4 paper, and the xenon lamp simulates sunlight. At the same time, the infrared thermal imager is used to measure the temperature change on the sample surface and take photos to record the experimental data. The light intensity is adjusted by adjusting the current of the xenon lamp and the distance between the light source and the sample surface. The light intensity is measured by a solar spectrum optical power meter.

[0043] Anti-icing performance experiment: The anti-icing test system built in the laboratory is used for measurement. The system mainly consists of semiconductor cryogenic cooling and monitoring system. The sample is placed close to the semiconductor refrigeration table, and the experimental working temperature is set to -15℃. After the surface of the sample is cooled to the set temperature, 10 μL deionized water drops fall on the surface of the sample to be tested, and the freezing process of the droplets is monitored by a CCD camera. By observing the morphological changes of the droplets on the surface of the sample to be tested, the time required for the droplets to completely freeze is obtained. The ice adhesion strength of the sample is measured by placing a plastic tube with a height of 2.5cm and a bottom radius of 5.5mm on the sample surface, injecting deionized water into the plastic tube and freezing it in a refrigerator for 12 hours. Use a digital thruster to push the icicle, record the peak thrust when the icicle separates from the sample surface, and calculate the ice adhesion strength on the sample surface:

[0044] τ ice =F m / A ice

[0045] Among them, τ ice is the adhesion strength of ice, A ice is the bottom area of ​​the ice.

[0046] Embodiments a to d

[0047] A method for preparing a titanium-based photothermal cotton fabric having a super-hydrophobic surface comprises the following steps:

[0048] X amount of TiN is dispersed in a certain amount of ethanol, ultrasonicated for 20-30 minutes, and then sprayed onto a 10×10 cm cotton fabric to obtain a TiN coated cotton fabric. The optimal TiN parameter is determined to be 2.2 wt % through Examples a-d.

[0049]

[0050]

[0051] Embodiments 1 to 5

[0052] A method for preparing a titanium-based photothermal fabric with a super-hydrophobic surface comprises the following steps:

[0053] 2.2wt% TiN was dispersed in ethanol and ultrasonicated for 20 to 30 minutes, and then sprayed onto a 10×10cm cotton fabric to obtain a TiN-coated cotton fabric, named TiN-CF. The fabric was then placed in an oven at 80 to 100°C and heated for at least 5 minutes to allow the ethanol to evaporate quickly, and the resulting coating was more uniform. PDMS and a curing agent were added to n-heptane (the mass ratio of PDMS, curing agent and n-heptane was 10:1:34) and the stirring time was at least 0.5h. Then the PDMS solution was sprayed for a second time, placed in an oven at 80 to 100°C, and pre-baked for 20 to 30 minutes. Finally, Y amount of H-SiO2-TiO2 JPs was dispersed in ethanol and sprayed for a third time. After multiple spraying, a super-hydrophobic photocatalytic fabric with photothermal conversion performance was obtained, named TiN-SCF. The optimal parameters of H-SiO2-TiO2 JPs were determined to be 1.75wt% by Examples 1 to 5.

[0054] Example Y Example 1 0.25wt% Example 2 0.5wt% Example 3 0.75wt% Example 4 1.00wt% Example 5 1.25wt% Example 6 1.5wt% Example 7 1.75wt%

[0055] Figure 1 Schematic diagram of the preparation process and photothermal anti-icing / de-icing application of the super-hydrophobic photocatalytic fabric of the present invention

[0056] Depend on Figure 2 It can be seen that the surface temperature of all samples increases with time. The temperature of the cotton surface rises slowly. Since TiN NPs have a high light absorption rate, the temperature response of the corresponding coating surface is faster. In addition, with the increase of H-SiO2-TiO2 JPs content, the maximum temperature within 300s drops from 70.2℃ to 64.5℃. When 1.25wt% is added, the temperature can rise to 66.2℃ in 300s, and the temperature increase is 43.6℃.

[0057] Depend on Figure 3 It can be seen from the temperature change curve of TiN-SCF under different light intensities that the surface temperature of the fabric is positively correlated with the light intensity. Under 1.5 suns, the equilibrium temperature of the fabric reaches 80.7°C, which is nearly 13°C higher than that under 1 sun.

[0058] Depend on Figure 4 It can be seen that the temperature change curve of TiN-SCF in the on-off illumination cycle shows that the surface temperature of the fabric rises or falls immediately after the xenon lamp is turned on or off, indicating that it has good light responsiveness. In each switching cycle, the surface temperature of the fabric changes in a consistent trend, proving that it has good light and thermal stability.

[0059] Depend on Figure 5 It can be seen that the droplets of milk, cola, water, hydrochloric acid solution with pH = 2 and sodium hydroxide solution with pH = 12 are all spherical and stand on the fabric surface, indicating that the fabric surface has good hydrophobicity.

[0060] Depend on Figure 6 It can be seen that after 6 hours of ultraviolet irradiation, the Rhodamine B on the pure cotton fabric was almost not degraded, while the degradation efficiency of the modified fabric on Rhodamine B could reach 64% within 6 hours.

[0061] Depend on Figure 7 It can be seen that the water droplets on pure cotton fabric (CF), hydrophobic pure cotton fabric (SCF), titanium-based photothermal fabric (TiN-CF) and titanium-based hydrophobic photothermal cotton fabric (TiN-SCF) have a longer delayed freezing time. Since TiN-SCF has about 600nm H-SiO2-TiO2 JPs and 20nm TiN NPs, the roughness is greater and more consistent with the Cassie model. Its delayed freezing time is better than SCF and has better anti-icing performance.

[0062] Figure 8 The figure shows the ice adhesion strength of different fabrics. The surfaces of CF and TiN-CF are relatively hydrophilic, and the contact area between the water droplet and the surface is larger, while the contact area between the SCF and TiN-SCF surfaces and the water droplet is small. Therefore, the latter two have lower friction coefficients and anti-adhesion properties, and lower ice adhesion strength.

[0063] Fig. 9 Schematic diagram of photothermal deicing of different fabrics. The ice on the TiN-SCF surface only takes about 120 seconds to melt into liquid, while the ice on the CF surface has not completely melted. This proves that the TiN-SCF surface has a higher photothermal conversion efficiency, which leads to faster ice melting efficiency.

[0064] Fig.10 The chemical stability and UV aging test diagram of Example 9 of the present invention is shown in FIG. Fig.10 (a) After the fabric was immersed in ethanol, hexane, acetone, pH=2 hydrochloric acid solution, and pH=12 sodium hydroxide solution for 24 hours, the contact angle was still greater than 150°. Fig.10 As can be seen in (b), after 24 h of UV aging, the WCA of the fabric is greater than 150°. The results show that TiN-SCF has excellent resistance to chemical solutions and UV stability.

[0065] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.

Claims

1. Titanium-based photothermal fabric with super-hydrophobic surface and preparation method thereof, characterized in that: The following steps are involved: 1) A certain amount of TiN is dispersed in ethanol, and is fully dissolved by ultrasonication, and then is uniformly sprayed on cotton fabric to obtain TiN-coated cotton fabric, which is named TiN-CF. The ratio of TiN to ethanol is (1.6-2.5): (97.5-98.4) by mass. 2) The TiN-CF fabric obtained in step 1) is placed in an oven for heating to allow the ethanol to evaporate quickly, so that the coating is more uniform. PDMS and curing agent are added to n-heptane and stirred. Then the PDMS mixed solution is sprayed evenly for the second time and placed in an oven for pre-baking. 3) A certain amount of Janus particles (H-SiO2-TiO2 JPs) were dispersed in ethanol, stirred at room temperature to fully dissolve, and then sprayed evenly for the third time. After multiple spraying, a super-hydrophobic photocatalytic fabric with photothermal conversion performance was obtained, named TiN-SCF. The ratio of H-SiO2-TiO2 JPs to ethanol was (0.25-1.75): (98.25-99.75).

2. The preparation method according to claim 1, characterized in that: In the step 1), the ultrasonic time is 20 to 30 minutes; In the step 1), the cotton fabric has a size of 10×10 cm.

3. The preparation method according to claim 1, characterized in that: In the step 2), the oven temperature is 80-100°C; In the step 2), the oven heating time is at least 5 minutes; In the step 2), the mass ratio of PDMS, curing agent and n-heptane is 10:1:34; In the step 2), the stirring time is at least 0.5h; In the step 2), the secondary oven temperature is 80-100°C; In the step 2), the secondary oven time is at least 20 minutes.

4. The preparation method according to claim 1, characterized in that: In the step 3), the stirring time is 1 to 2 hours.

5. A super-hydrophobic photocatalytic fabric with light-to-heat conversion performance obtained by the preparation method as described in any one of claims 1 to 4.

Citation Information

Cited By

  • Hydrophilic substrate and TiN composite photothermal conversion material and preparation method and application thereof

    CN122010221A